2021
DOI: 10.1056/nejmoa2109072
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Breakthrough Infections in Vaccinated Health Care Workers

Abstract: Background Despite the high efficacy of the BNT162b2 messenger RNA vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rare breakthrough infections have been reported, including infections among health care workers. Data are needed to characterize these infections and define correlates of breakthrough and infectivity. Methods At the largest medical center in Israel, we identified breakthrough infections by performing extensive evaluations of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,108
9
13

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,307 publications
(1,281 citation statements)
references
References 23 publications
60
1,108
9
13
Order By: Relevance
“…Here, we demonstrate for the first time a clear correlation between adverse reactions and antibody levels. Recent studies showed that higher antibody levels are correlated with protection from symptomatic SARS-CoV-2 infection [11][12][13]. Therefore, our findings indicate that non-serious adverse reactions may be predictive of a favorable anti-COVID-19 protective effect.…”
Section: Discussionsupporting
confidence: 51%
“…Here, we demonstrate for the first time a clear correlation between adverse reactions and antibody levels. Recent studies showed that higher antibody levels are correlated with protection from symptomatic SARS-CoV-2 infection [11][12][13]. Therefore, our findings indicate that non-serious adverse reactions may be predictive of a favorable anti-COVID-19 protective effect.…”
Section: Discussionsupporting
confidence: 51%
“…At low levels of antibodies, the lungs appear to remain relatively protected against severe disease presumably by some combination of antibodies and amnestic responses restimulated by the time the lung is involved. In contrast, the early establishment of infection in the upper respiratory tract appears possible if antibody levels are low (47). We therefore postulate that variants that are more effective in interfering with Type 1 interferon responses would be more transmissible, but not necessarily cause severe disease in the context of waning immunity at an individual or population level.…”
Section: Resultsmentioning
confidence: 99%
“…A large proportion of SARS-CoV-2 infections are asymptomatic 6 , and our results indicate that seropositivity alone is not sufficient to predict a robust antibody response to vaccination. Recent data suggest that lower responses to vaccination are associated with increased risk of breakthrough infection: Among vaccinated healthcare workers in Israel monitored from January to April 2021, neutralizing antibody and anti-spike IgG titers were significantly lower in workers with breakthrough infections in comparison with matched, uninfected controls 7 . The B.1.1.7 variant was detected in 85% of the breakthrough infections.…”
Section: Discussionmentioning
confidence: 99%